Matrix cracking in reinforced polymer nanocomposites: a review - Khalid, Muhammad Ilham; Anuar, Hazleen; Shaffiar, Norhashimah; Yaacob, Iskandar Idris; Mohd. Salit, Sapuan (Penerbit Akademia Baru, 2015)
This paper presents a summary about the problem of matrix cracking in reinforced polymer nanocomposite materials. The matrix cracking is reviewed under condition of fatigue loading, tensile loading, thermal loading, and flexural loading mechanism. Moreover, it discussed the effect of the matrix cracking on the material damping property and how the crack growth in the matrix nanocomposite materials is predicted. Fatigue life of the nanocomposite is also discovered after the crack propagation in matrix of nanocomposite is predicted. Continuum damage mechanics are discussed and used to prove the behaviour of the cracked matrix nanocomposite. Current development in this area is briefly discussed